Sanctions and Democratization in the Post-Cold War Era - Christian von Soest; Michael Wahman (German Institute of Global and Area Studies (GIGA), 2013)
Previous research, which has focused mostly on pre-1990 dynamics, has shown that sanctions have a negative impact on the level of democracy in targeted authoritarian countries. Given this finding, it is puzzling that democratization has become the most common goal of sanctions issued against authoritarian states. This paper studies how sanctions have affected democratization in targeted countries since the end of the Cold War and asks whether democratic sanctions, those that explicitly aim to promote democracy, are in fact counterproductive. Contrary to the earlier research, this analysis demonstrates that sanctions do not generally decrease the level of democracy in targeted countries. Using a new data set covering sanctions for the period 1990-2010 and cross-sectional time-series analysis, the study shows that sanctions have an insignificant but positive democratic effect. More importantly, it finds that democratic sanctions have a statistically significant positive effect on democratic development in targeted countries. This positive outcome can be explained by the smaller selection effect associated with this specific sanction type. The high cost of conceding to democratic sanctions makes authoritarian regimes less likely to give in to senders' demands before sanctions are implemented. The high-cost argument is corroborated by a supplementary test that demonstrates that democratic sanctions in particular make authoritarian institutions and rulers more instable.
Keywords: 300; sanctions; authoritarian regimes; persistence; regime change; ruler exit; concession costs; post-Cold War era